Efecto de diferentes tiempos de activación y desactivación de trampas Sundance sobre la producción de polen en colmenas de Apis mellifera L. - Leiva Chimbor, Luis Andres (2018)
The present work was carried out with the objective of determining the effect caused by the activation and deactivation times of Sundance traps on pollen production in hives of Apis mellifera L., in Chao, Virú. We used 20 colonies of bees with homogeneous populations in Langstroth type hives and each one was placed a trap, 4 treatments were performed, each corresponding to 5 hives with traps that were permanently activated (T0), activated / deactivated every 7 days (T1), every 14 days (T2) and 21 days (T3), respectively. The pollen harvest was carried out every three days during the months of June to September 2017. Pollen production was recorded for each treatment, of 7,186 kg, 4,240 kg, 5,112 kg and 8,764 kg of pollen for treatments T0, T1, T2 and T3 respectively; an average of pollen harvested per hive of 1,437 kg, 0,848 kg, 1,022 kg was found; 1,753 kg for the treatments T0, T1, T2, T3 respectively. The Analysis of Variance was made and differences were found between treatments, and through the Tukey test, highly significant differences were found between the treatments T3 - T0, T3 - T1 and T3 - T2. It is concluded that the activation and deactivation of the Sundance pollen traps every 21 days allowed a greater pollen production and that the permanent activation of said trap causes a decrease in the bee population.